Canonising the Shakespeare apocrypha: Shakespeare, Middleton and co-existent canons - Kirwan, Peter (Blackwell Publishing, 2012)
The Shakespeare Apocrypha has persisted as a category for plays of dubious authorship since 1908. Despite recent calls for this group to be dissolved, it persists as the “other” of the Shakespeare canon. The definition of the plays as a collectively excluded canon leads to their relative obscurity in print and on stage. Yet recent calls for the adoption of different kinds of dramatic canon present a means of reintegrating canon and apocrypha. The new Middleton Collected Works offers a model for “co-existent canons” which share plays and disperse the authority of fixed authorial canons, allowing the plays of the Shakespeare Apocrypha to be read and seen in new, productive contexts.